Validation of the GAEU-1 Acale to Assess the Learning Management of University Students - Carlos Ramos-Galarza; Patricia García-Cruz; Nancy Lepe-Martínez; Milenko Del Valle; Mónica Bolaños-Pasquel; Jorge Cruz-Cárdenas (Emerging Science Journal, 2023)
Introduction: The self-management of university learning encompasses a series of aspects that allow students to be conscious and autonomous in their professional training. Objective: In this article, we present the process of creation and validation of a scale to assess essential factors of this phenomenon: self-management of learning, conscious motivation strategies for learning, perception of academic performance, and techniques for deep learning. Method: The design is a cross-sectional quantitative process with the purpose of carrying out validity and reliability analysis of a psychological measurement instrument. The research was conducted with 1373 university students from Chile and Ecuador. Results: The scale consists of 19 items that conform the four factors mentioned and whose results indicate adequate psychometric properties, allowing it to be applied in the Latin American context. Novelty:This research proposes a new instrument to assess the self-management of the university learning process, which contributes to carrying out new research in the university educational context. Doi: 10.28991/ESJ-2023-SIED2-019 Full Text: PDF